Pigeon-Raven and sperm whale, magical objects and domestic horned - Cassen, Serge (Documenta Praehistorica, 2005)
We are going to demonstrate that it is possible to invest an Armorican stele of the 5th millennium with an order of meanings in the same way as a language or a kinship system; in other words, a set of operations destined to ensure, between individuals and groups, a certain type of communication. But such demands necessitate modifying established patterns, because none agree on the idea that we have conceived of a peaceful passage to agriculture and animal husbandry on the Atlantic façade of Europe. Each fundamental sign on these standing stones will here be reconsidered, and their 'syntax' analysed. However, we have no innocence about the subject: as soon as we display the strange desire to question these engravings, we 'participate' in an analogicalspell attributed to a distant image, we fall as well into those exegetic attempts which pretend to obey to a cultural project wherein it appears they interpret the symbolism but that, finally, tend to renew it, because any key to symbols is part of their symbolism. And even in an oneiric or fair world, power does not derive from gratuitousness, but from coherence.
Keywords: arheološke najdbe; neolitik; communication; komuniciranje; govor; simboli; symbol; Velika Britanija